Leadership is a conversation : how to improve employee engagement and alignment in today's flatter, more networked organizations - Groysberg, Boris
Presents the findings of a research project which reveals that traditional corporate communication must give way to a process that is more dynamic and sophisticated viz, to have a conversation or to advance the conversation. Describes the model of leadership as "organizational conversation," and discusses the four elements identified, i.e. intimacy, interactivity, inclusion and intentionality.